Deviations from NIRS-derived optimal blood pressure are associated with worse outcomes after pediatric cardiac arrest. (November 2021) - Kirschen, Matthew P.; Majmudar, Tanmay; Beaulieu, Forrest; Burnett, Ryan; Shaik, Mohammed; Morgan, Ryan W.; Baker, Wesley; Ko, Tiffany; Balu, Ramani; Agarwal, Kenya; Lourie, Kristen; Sutton, Robert; et al.
Abstract: Aim: Evaluate cerebrovascular autoregulation (CAR) using near-infrared spectroscopy (NIRS) after pediatric cardiac arrest and determine if deviations from CAR-derived optimal mean arterial pressure (MAPopt ) are associated with outcomes. Methods: CAR was quantified by a moving, linear correlation between time-synchronized mean arterial pressure (MAP) and regional cerebral oxygenation, called cerebral oximetry index (COx). MAPopt was calculated using a multi-window weighted algorithm. We calculated burden (magnitude and duration) of MAP less than 5 mmHg below MAPopt (MAPopt - 5), as the area between MAP and MAPopt - 5 curves using numerical integration and normalized as percentage of monitoring duration. Unfavorable outcome was defined as death or pediatric cerebral performance category (PCPC) at hospital discharge ≥3 with ≥1 change from baseline. Univariate logistic regression tested association between burden of MAP less than MAPopt - 5 and outcome. Results: Thirty-four children (median age 2.9 [IQR 1.5, 13.4] years) were evaluated. Median COx in the first 24 h post-cardiac arrest was 0.06 [0, 0.20]; patients spent 27% [19, 43] of monitored time with COx ≥ 0.3. Patients with an unfavorable outcome ( n  = 24) had a greater difference between MAP and MAPopt - 5 (13 [11, 19] vs. 9 [8, 10] mmHg, p  = 0.01) and spent more time with MAP below MAPopt - 5 (38% [26, 61] vs. 24% [14, 28], p  = 0.03). Patients with unfavorable outcome had a higher burden of MAP less than MAPopt - 5 than patients with favorable outcome in the first 24 h post-arrest (187 [107, 316] vs. 62 [43, 102] mmHg × Min/Hr; OR 4.93 [95% CI 1.16–51.78]). Conclusions: Greater burden of MAP below NIRS-derived MAPopt - 5 during the first 24 h after cardiac arrest was associated with unfavorable outcomes.